1988
DOI: 10.1007/bf01746610
|View full text |Cite
|
Sign up to set email alerts
|

Cytochemical studies of hydrogen peroxide production in the tadpole tail ofRana japonica during metamorphic climax

Abstract: The degeneration of tadpole tail tissue was investigated cytochemically by localizing the sites of hydrogen peroxide production. A cerium perhydroxide precipitation method was used. No reaction product was found in resting macrophages and intact muscle fibres during premetamorphosis. In the metamorphosis phase, extensive cerium precipitates were visualized on the outer surface of the plasma membrane of phagocytotic macrophages, fibroblasts, neutrophils, epidermal cells, muscle fibres, notochordal cells, nerve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…It has been reported that hydrogen peroxide locates on the plasma membrane at the sites of contact between macrophages and adjoining cells in the tails of metamorphosing R. japonica tadpoles. 25 In our study, we found increased SOD and CAT activities during the developmental period in R. r. ridibunda and B. viridis tadpoles and similar reports have also been published for some other animals during early development such as the fruit fly C. capitata, 26 and guinea pig. 31 Increases of antioxidant enzyme activities can reflect altered gene expression during development and synthesis of these proteins.…”
Section: Discussionsupporting
confidence: 84%
“…It has been reported that hydrogen peroxide locates on the plasma membrane at the sites of contact between macrophages and adjoining cells in the tails of metamorphosing R. japonica tadpoles. 25 In our study, we found increased SOD and CAT activities during the developmental period in R. r. ridibunda and B. viridis tadpoles and similar reports have also been published for some other animals during early development such as the fruit fly C. capitata, 26 and guinea pig. 31 Increases of antioxidant enzyme activities can reflect altered gene expression during development and synthesis of these proteins.…”
Section: Discussionsupporting
confidence: 84%
“…Tail resorption begins from Taylor and Kollros (1946) (TK) stage XX (Sasaki et al, 1988) and death of tail tissues predominantly involves apoptosis of cell followed by phagocytosis of cell debris by macrophages and other cells (Kerr et al,1974;Gilbert and Frieden, 1981). Macrophages remove the cell debris resulting out of muscle and epidermal degradation (Kinoshita et al, 1985;Nishikawa et al, 1998) whereas fibroblasts contribute in the removal of collagenous components of tail like the notochord and the basement membrane (Berry et al, 1998).…”
Section: Introductionmentioning
confidence: 99%